Kinetic Adsorption of CO2/CH4 Mixture using 13X Zeolite: Modeling and Simulation - Awah Nouh, Salma (David Publishing Company, 2010)
In this work, the separation of carbon dioxide (CO2) from the methane (CH4) using fixed bed Pressure Swing Adsorption (PSA) column was modeled and simulated. The adsorption kinetics on the 13X zeolite adsorbent was described by Linear Driving Force (LDF) model. Simulation of adsorption phenomena inside the fixed bed was implemented using Computational Fluid Dynamic (CFD) method, based on porous media concept, and the mass transfer coefficients for gas components (CO2 and CH4) were developed using User Defined Scalars (UDS). The model was validated by comparing with the experimental data, which were collected based on a varied set of laboratory conditions. The prediction of the adsorption isotherm (uptake curve) and methane recovery using the simulation results exhibited a reasonable agreement with the experimental data. Moreover, the effects of feed flow rate and bed concentration evolution were investigated. The current results suggested that CFD approach is capable to predicate the hydrodynamics and adsorption phenomena in the fixed bed adsorption column.